The snowy ride - Davis, Lee, 1941- (New York : DK Pub., 1996)
After pulling on his warmest socks, boots, sweater, wooly scarf, and hat, P.B. Bear steps out into the snow and Dermott arrives with a sled.
Keywords: Teddy bears -- Fiction; Toys -- Fiction; Snow -- Fiction; Sleds -- Fiction